Continuous flow multipoint dosing approach for selectivity engineering in sulfoxidation - Kulkarni, A. A.; Nivangune, N. T.; Joshi, Rohini R.; Joshi, Ramesh A. (Organic Process Research & Development, 2013)
A continuous synthesis approach with multipoint dosing of one of the reagents is demonstrated for the synthesis of sulfoxide compounds such as proton pump inhibitors. Use of multipoint dosing of the oxidizing agent helped to minimize the possibility of over-oxidation leading to sulfone. Different oxidizing agents were used, and the effect of various parameters (viz. mole ratio of sulfide to oxidizing agent, temperature, residence time, concentration of oxidizing agent, etc.) on the yield of the desired sulfoxide compound was studied. Single-point and multipoint dosing approaches of the oxidizing agent were used for the most promising set of parameters. The performance was compared in terms of conversion of sulfide and the selectivity of the desired sulfoxide. Numbering up approach was used to produce the sulfoxide in a relatively large quantity at laboratory scale with complete conversion and over 99% selectivity for the sulfoxide.

MgFeCe ternary layered double hydroxide as highly efficient and recyclable heterogeneous base catalyst for synthesis of dimethyl carbonate by transesterification - Nivangune, N. T. (Catalysis Letters, 2017)
A series of Mg3:Fex + Ce1−x LDHs (3:1) were synthesized by co-precipitation method by varying molar ratio of Fe:Ce between 1:0 to 0:1 (LDH-1 to LDH-6). All synthesized LDHs were characterized by XRD, FT-IR, TEM, N2 sorption, benzoic acid titration and XPS in detail and evaluated for selective synthesis of dimethyl carbonate by transesterification of ethylene carbonate with methanol. It was demonstrated that the structural and basic properties of synthesized LDHs were strongly dependent on the Fe:Ce molar ratio (Ce concentration). The correlation between their physicochemical properties and catalytic performance was studied in detail. Among all synthesized LDHs the best result was obtained with LDH-3 (Fe:Ce = 0.85:0.15) where LDH structure remained intact, and showed high number of strong basic sites on LDH surface. LDH-3 was recycled 7 times while maintaining high catalyst activity and selectivity towards DMC. The obtained results elucidate the important role of Ce in modifying the basic properties of LDH in enhancing the catalytic activity for DMC synthesis. Graphical Abstract: [Figure not available: see fulltext.]. © 2017, Springer Science+Business Media, LLC.
Keywords: Dimethyl carbonate; ethylene carbonate; Mg–Fe–Ce Ternary Hydrotalcite; transesterification